Pengaruh Minat Beli Dan Daya Saing Terhadap Peningkatan Penjualan Pada Jasa Titip Instagram @Jastipdiskon.Medan - Sembiring, Bellen Viebiola; Waruwu, Khamo; Pakpahan, Evalina; Lubis, Hilman (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
This study was conducted by looking at the phenomenon of online shopping services that are currently growing. So the researcher aims to analyze the influence of Purchase Interest and Competitiveness on Sales Increase in Instagram online shopping services @Jastipdiskon.Medan. The background of this study is based on problems related to consumer purchasing interest and lack of competitiveness that can result in decreased sales. This study uses a quantitative method with a customer population of @Jastipdiskon.Medan of 80 people. The sampling technique was carried out using the Simple Random Sampling (Slovin) method. Purchase interest and competitiveness factors have been shown to have a significant influence on increasing sales. These results are presented to provide input for the same type of business so that it can continue to grow and the possibility of other factors that can affect sales such as great competition due to the increasing number of online shopping services today